Mitochondrial dynamics and quantification of mitochondria‐derived vesicles in cardiomyoblasts using structured illumination microscopy. Issue 2 (23rd November 2021) - Opstad, Ida S.; Godtliebsen, Gustav; Ahluwalia, Balpreet Singh; Myrmel, Truls; Agarwal, Krishna; Birgisdottir, Åsa Birna
Abstract: Mitochondria are essential energy‐providing organelles of particular importance in energy‐demanding tissue such as the heart. The production of mitochondria‐derived vesicles (MDVs) is a cellular mechanism by which cells ensure a healthy pool of mitochondria. These vesicles are small and fast‐moving objects not easily captured by imaging. In this work, we have tested the ability of the optical super‐resolution technique 3DSIM to capture high‐resolution images of MDVs. We optimized the imaging conditions both for high‐speed video microscopy and fixed‐cell imaging and analysis. From the 3DSIM videos, we observed an abundance of MDVs and many dynamic mitochondrial tubules. The density of MDVs in cells was compared for cells under normal growth conditions and cells during metabolic perturbation. Our results indicate a higher abundance of MDVs in H9c2 cells during glucose deprivation compared with cells under normal growth conditions. Furthermore, the results reveal a large untapped potential of 3DSIM in MDV research. Abstract : This article shows how to use the super‐resolution technique 3DSIM in combination with machine learning‐based segmentation to measure the number of mitochondria‐derived vesicles in living or fixed cells. The number of vesicles in cardiomyoblasts is compared for two different growth conditions (glucose and galactose). Further, the 3DSIM videos presented show rapid dynamics of mitochondria‐derived tubules and vesicles at unprecedented resolution and contrast.